'Halomonas saudii' sp. nov., a new bacterial species isolated from marine plant Halocnemum strobilaceum. (January 2017) - Bibi, F.; Yasir, M.; Alvi, S.A.; Azhar, E.I.; Al-Ghamdi, A.A.K.; Abuzenadah, A.M.; Raoult, D.; Angelakis, E.
Abstract: We report here the main characteristics of ' Halomonas saudii ' strain Saudii DR2 (CSUR P2512), a new species of the Halomonas genus that was isolated from a rhizosphere of Halocnemum strobilaceum in April 2015.